2009
DOI: 10.1002/anie.200805739
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Halogen⋅⋅⋅Halogen Interactions: A Model Derived from Experimental Charge‐Density Analysis

Abstract: Slightly attractive: The attractive and anisotropic nature of the ClCl interaction in C(6)Cl(6) is experimentally demonstrated from an expansion of the electron density rho(r) around the chlorine nuclei. The interaction is explained in a model in which there is a bonding attraction involving electron-deficient (see picture, blue) and electron-rich (red) regions of adjacent Cl atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
303
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(327 citation statements)
references
References 37 publications
23
303
1
Order By: Relevance
“…3a), in which the molecules are related by a 2-fold screw axis. The intermolecular separation Cl1Á Á ÁCl2 is 3.557(2) Å, value barely larger than twice the spherical chlorine van der Waals radius (3.52 Å) and in agreement with several reported structures where these kinds of interactions were considered [13]. The C5-Cl1Á Á ÁCl2 and C10-Cl2Á Á ÁCl1 angles are 112.43°a nd 158.35°, respectively, with a u dihedral angle of 73.82°.…”
Section: Molecular and Supramolecular Structuresupporting
confidence: 89%
See 1 more Smart Citation
“…3a), in which the molecules are related by a 2-fold screw axis. The intermolecular separation Cl1Á Á ÁCl2 is 3.557(2) Å, value barely larger than twice the spherical chlorine van der Waals radius (3.52 Å) and in agreement with several reported structures where these kinds of interactions were considered [13]. The C5-Cl1Á Á ÁCl2 and C10-Cl2Á Á ÁCl1 angles are 112.43°a nd 158.35°, respectively, with a u dihedral angle of 73.82°.…”
Section: Molecular and Supramolecular Structuresupporting
confidence: 89%
“…Ab initio calculations in concordance with experimental crystallographic studies showed that in the basis of an electrostatic model, halogenÁ Á Áhalogen contacts are directive and a result of attractive forces for all halogens (except fluorine) [12]. A recent study based on experimental chargedensity analysis concluded that although Type I geometries are of the van der Waals kind where the dispersion term of the interaction energy prevails on the electrostatic one, the Type II contacts may be understood as attractive X d+ Á Á ÁX dÀ interactions [7,13]. Other area developed by crystal engineers is the understanding of polymorphism, phenomenon in which a single molecular compound has two or more crystal assembly [14].…”
Section: Introductionsupporting
confidence: 62%
“…The strength of this bond is however strongly depending of its geometry. 28 Hydrogen-1 , 3 − 1 2 , 1 4 , 1 5 , 2 9 − 3 4 as well as halogenbonded 3,22,23,26,27,35−47 organic nanoarchitectures have been successfully engineered in vacuum but also at the solid/liquid interface. In that case the solvent nature 48−50 and molecular concentration can drastically affect the structure of the organic layer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, fluorine-containing compounds are important for life and material sciences [10][11][12]. Fluorine is comparable to hydrogen atom in size but, possesses different physical and chemical properties, and capable of forming strong halogen bonds [13][14][15][16][17][18][19]. The latter can be of different motifs, such as F···F, F···N, and F···C intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%